INVENTARISASI BAHASA-BAHASA DAERAH DI PROPINSI NUSA TENGGARA TIMUR - Inyo Yos Fernandez (Humaniora, 2007)
The inventarisation to understand the number and status of languages dialects in East Nusa Tenggara should be conducted using the right theory and methodology. The inventarisation should be done by implementing quantitavie and qualitative approaches so that satisfactory results can be achieved in the process of inventarisation in the future. Despite the fact that there may be some weaknesses in the use of the quantitative approach to determine family language using kexicostatistics technique, the result may provide clear and reliable descriptions of the NTT family language